Parricídio: um estudo de caso - Teixeira, Lívia Pinho (2016)
Parricide is the homicide committed by children against their own parents. The term covers acts of patricide, which is the murder of one’s father by one of his own children, and matricide, when one murders their own mother. The following is a case study which was conducted through individual psychotherapy with a patricide and whose objectives were: understanding the behavior of the therapist and establishing rapport; tracing educational and professional background of the subject; tracing the existance of psychological and physical abuse; studying the existance of motherly acts of protection; collecting data of crime day and its determinants; sheding light on parental practices. A 19-year-old male who committed homicide against his own father was the subject of this research in various settings. The data were gathered in the course of 18 sessions, through the use of questionnaires and analysis of both his criminal and the lawsuit court records, which are put forward as a case study were discussed and analyzed through a theoretical framework. Following that, section two was analyzed on the IRAMUTEQ software. Both parents were given a parental risk index and 10 categories which account for a childhood of physical and emotional abuse and negligence were identified. The current work emphasizes the need to study and describe forms of intervention which seek to promote the parricide’s social reintegration.